Penerapan Project Based Learning dengan Lesson Study untuk Meningkatkan Hasil Belajar Teknik Pemesinan - Bastian Rikardo Parhusip; Bernadus Sentot Wijanarka (Department of Mechanical Engineering Education, 2018)
This study aims to: (1) promote students to become active and skillful, (2) improve students' knowledge, and (3) improve students' skills through the implementation of project-based learning (PjBL) by lesson study on milling machining subject. This research used quasi-experiment research method with one group pretest-posttest design. To test the hypothesis, data were analyzed using paired sample t-test incorporating Wilcoxon test technique aided with SPSS 20. The results show that: (1) lesson study promotes active and skilled students. It is observed that student activeness is above 90% (